HUBUNGAN LAMA PEMBERIAN DIET ATEROGENIK TERHADAP KADAR TRIGLISERIDA Rattus novergicus JANTAN STRAIN WISTAR - Renti Sulvia Niza; Enikarmila Asni; Wiwit Ade Fidiawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTCardiovascular diseases is the disruption and damage of the heart muscleand the number one cause of death worldwide. Based on epidemiologic data andclinical trial results support an association between elevated triglyceride andCardiovascular risk. The goal of this research is to know the correlation of givenduration atherogenic diet againts triglyceride level in male wistar rats. Thisresearch was experimental with the post test-only control group design, by usingmale rats (Rattus novergicus) of 2-3 month with the average weight range of 160-240 g. The rats were divided into 4 group, control group given with standard diet,the 5 weeks atherogenic diet group, the 8 weeks atherogenic group and 12 weeksatherogenic group, in which group consist of 6 rats. The atherogenic diet (2%cholesterol of yolk, 5% goat’s fat, and 0,2% cholic acid) were given as much as20 g/each/day. The result showed a significant difference (p=0,000). As for thepost hoc test (p=0,000), there is a statistically significant difference within theexperimental groups. As for the spearman test (0,969), it shows a significantpositive correlation between the given duration of the atherogenic diet and thetriglyceride level. It can be concluded the longer time that the rats gotatherogenic diet showed the level of triglycerides rats (Rattus novergicus)increased.Keywords: Atherogenic diet, triglyceride level, rats (Rattus novergicus).